Managing cultural differences - Harris, Philip R.,Moran, Robert T.,Moran, Sarah V. (Elsevier, 2004)
This new edition has been completely updated to reflect the numerous global changes that have occurred since 1999: globalization, SARS, AIDS, the handover of Hong Kong, and so forth. In particular, the book presents a fuller discussion of global business today. Also, issues of terrorism and state security as they affect culture and business are discussed substantially. The structure and content of the book remains the same, with thorough updating of the plentiful region and country descriptions, demographic data, graphs and maps. This book differs from textbooks on International Management because it zeroes in on culture as the crucial dimension and educates students about the cultures around the world so they will be better prepared to work successfully for a multinational corporation or in a global context.
Keywords: Lehrbuch; Aculturación; Culturele verschillen; Empresas internacionales - Administración; Entreprises multinationales - Gestion; Estudios interculturales; Internationaal bedrijfsleven; Leiderschap; Strategisch management; Éducation au développement; Études transculturelles; Multinationales Unternehmen; Acculturation; Cross-cultural studies; International business enterprises; Interkulturelle Kompetenz; Interkulturelles Management; Kulturkreis; Ausland; Akkulturation; Management; Internationales Management